A companion to Venetian history, 1400-1797 - Dursteler, Eric.
1 online resource (992 pages)
Keywords: The field of Venetian studies has experienced a significant expansion in recent years, and the Companion to Venetian History, 1400-1797 provides a single volume overview of the most recent developments. It is organized thematically and covers a range of topics including political culture, economy, religion, gender, art, literature, music, and the environment. Each chapter provides a broad but comprehensive historical and historiographical overview of the current state and future directions of research. The Companion to Venetian History, 1400-1797 represents a new point of reference for the next generation of students of early modern Venetian studies, as well as more broadly for scholars working on all aspects of the early modern world. Contributors are Alfredo Viggiano, Benjamin Arbel, Michael Knapton, Claudio Povolo, Luciano Pezzolo, Anna Bellavitis, Anne Schutte, Guido Ruggiero, Benjamin Ravid, Silvana Seidel Menchi, Cecilia Cristellon, David D’Andrea, Elisabeth Crouzet-Pavan, Wolfgang Wolters, Dulcia Meijers, Massimo Favilla, Ruggero Rugolo, Deborah Howard, Linda Carroll, Jonathan Glixon, Paul Grendler, Edward Muir, William Eamon, Edoardo Demo, Margaret King, Mario Infelise, Margaret Rosenthal and Ronnie Ferguson.